The Depiction of Putin’s Power and Dominance in Political Cartoons about Russia-Ukraine War - Nasira, Nurina; Syahriyani, Alfi; Abdurossyid, Abdurrosyid (Buletin Al-Turas, 2025)
PurposeThis study aimed to investigate the depiction of Vladimir Putin’s Power and Dominance in political cartoons collected from usnews.com, and identified the social contexts underlying the creation of those political cartoons. MethodThis research used qualitative methods which engaged in discovering and uncovering the meaning of a particular phenomenon. The sample data was three political cartoons related to the Russia-Ukraine War taken from usnews.com. It employed Multimodal Discourse Analysis (MDA) approach of Visual Grammar from Kress & Leeuwen (2006) to examine the visual mode, and Systemic Functional Grammar theory from Halliday & Matthiessen (2014) to analyze the verbal modes. Results/findingsThe findings showed that Vladimir Putin in political cartoons was represented as a negative powerful figure through the dominant use of the narrative process. Whilst the images of Putin as a ruthless and dictator figure were revealed in the verbal modes through the use of material, relational, and mental process. Each political cartoon's social context connects the visual and verbal modes while providing clearer information about the reason for cartoonists created these political cartoons. The partiality of the American cartoonists to the United States and Western countries also revealed through the political cartoons that worked as a medium to convey the cartoonists’ thoughts, showing that they fought against the invasion. ConclusionThrough visual and verbal analysis, the cartoonist constructed a negative portrayal of Vladimir Putin as a dictatorial leader. However, this study has limitations in its scope since it does not deeply address potential variations in viewer or audience’s interpretation based on individual backgrounds and experiences. Therefore, future researchers are encouraged to expand upon this study by exploring the production and consumption of similar texts, which may offer diverse or multiple perspectives on the subject.